Nanotechnology applications in environmental engineering - Nazir, Rabia, 1977- (Engineering Science Reference, 2019)
"This book provides a comprehensive look at the nanomaterials and their impact on environment. It also covers areas such as emission reduction, environmental remediation and monitoring, water and wastewater treatment, energy conversion and storage as well as alternative energy and toxicology"--